Glycolytic Metabolism Is Critical for the Innate Antibacterial Defense in Acute Streptococcus pneumoniae Otitis Media - Fan, Fangmei; Ma, Yurong; Ai, Rongshuang; Ding, Zhiqiang; Li, Dingyi; Zhu, Yiting; He, Qian; Zhang, Xinxin; Dong, Yilin; He, Yujuan (Frontiers in Immunology, 2021)
Objective Streptococcus pneumoniae (S.pn) is a common respiratory pathogen and a frequent cause of acute otitis media (AOM) in children. However, little is known about the immunometabolism during AOM. This study was to assess the presence of glucose metabolic reprogramming during AOM and its underlying mechanism affecting inflammatory response and middle ear injury. Methods The levels of glycolytic metabolism were evaluated by measuring the expression of glycolysis-related genes and the production of metabolites. HE stain, immunofluorescence, immunohistochemistry, enzyme-linked immunosorbent assay (ELISA) and western blot were performed to measure the effect of glucose metabolic reprogramming on inflammatory response, pneumococcal clearance, HIF-1α expression and cytokine secretion during AOM, respectively. Results The analysis of microarray revealed an increase of the expression of glycolysis-related genes during S.pn induced AOM, which was verified by real-time PCR. Increased glycolysis promoted the production of IL-1β and TNF-α and facilitated the clearance of S.pn by enhancing phagocytosis and killing capability of neutrophils, but also aggravated the middle ear injury. Furthermore, these pathogenic effects could be reversed after glycolytic inhibitor 2DG treatment. Additionally, hypoxia inducible factor 1 alpha (HIF-1α) were observed to involve in glycolytic metabolism during AOM. Conclusion S.pn infection induced increased glycolysis conversion during AOM, which promoted inflammatory responses and bacterial clearance, but also aggravated tissue damage.